Inventory and the biogeographical affinities of Annelida Polychaeta in theAlgerian coastline (Western Mediterranean) - BAKALEM, ALI; GILLET, PATRICK; PEZY, JEAN-PHILIPPE; DAUVIN, JEAN-CLAUDE (Mediterranean Marine Science, 2020)
The data analyzed to inventory of all polychaetes in Algerian waters make it possible to estimate the diversity of this group to 534 species. The most diversified families are Syllidae (66 species), Spionidae (37 species) and Terebellidae (27 species).The presence of these listed species along the Algerian coast is compared with their occurrence in nine other areas of the Mediterranean Sea, in the Black Sea and in four other areas of the World Ocean. Comparison are also made with respect to the indications of the biogeographical origin for each species. The polychaete fauna of the Algerian coast is among the richest of the Mediterranean Sea and comparable to that reported for the French Mediterranean continental shelf and the Aegean Sea, but higher that that found in the bordering coastlines of Morocco and Tunisia. Most of the species have an Atlantic origin and are present in the western Mediterranean Sea; this inventory includes eight Non-Indigenous Polychaete Species in the Algerian waters.